Impact of BRDB Micro-credit towards Uplifting Social Status of the Beneficiaries - Sarker, R. D.; Ali, M. S.; Islam, M. R.; Alam, M. M. (International Journal of Bio-resource and Stress Management, 2010)
The specific objective of the study was to determine the impact of BRDB micro-credit towards uplifting the social status of the beneficiaries measured by computing change in ‘income’, ‘food consumption’, ‘housing unit’, ‘drinking water source and toilet condition’, and ‘family asset’. Attempts were also made to determine and describe ten selected profiles of BRDB beneficiaries, and to explore the relationship between these profiles and impact of micro-credit. This study also identified the problems faced by the beneficiaries in receiving and utilizing micro-credit. The study was conducted at Naikhongchhari in Bandarban district of Bangladesh. The findings indicated that most (60%) of the respondents could change their socio-economic status to medium scale compared to 38% in low and 2% in high scale after involvement with BRDB micro-credit programs. Beneficiaries’ education, farm size, organizational participation with BRDB, yearly savings, credit received and attitude towards BRDB micro-credit had positive and significant relationship with the impact of BRDB micro-credit while age, family size, credit utilization, credit recovery procedure had not any significant relationship with the impact of micro-credit towards uplifting the social status of the beneficiaries. On the basis of the Problem Facing Index (PFI) ‘do not get current credit when any one of them did not repay previous loan’ was ranked first followed by ‘insufficient amount of credit’ whereas ‘decisions taken based on nepotism’ was ranked last.